Prevalence and Severity of Oral Diseases in the Africa and Middle East Region. (July 2015) - Abid, A.; Maatouk, F.; Berrezouga, L.; Azodo, C.; Uti, O.; El-Shamy, H.; Oginni, A.
This review aims to determine the prevalence and severity of oral health diseases in the Africa and Middle East region (AMER). The profile of oral diseases is not homogeneous across the AMER. There are large disparities between groups. Reliable data are scarce. The prevalence and severity of oral diseases appear to be increasing in the African region, as does associated morbidity. There are substantial differences in inequalities in oral health. Dental caries prevalence is less severe in most African countries than in developed countries, but the high rate of untreated caries reflects the limited resources available and difficulties of access and affordability to essential oral health care services. The prevalence of gingival inflammation is very high in all age groups in several African countries. The prevalence of maxillofacial trauma has increased in many countries, with a wide variation of the incidence and high prevalence of traumatic dental injuries in primary and permanent teeth. Orofacial clefts are among the most common birth defects. Annual incidence of oral cancer is estimated as 25 cases per 100, 000 people in Africa. Noma is a major public health problem for the Middle East and North African (MENA) region. Data about human immunodeficiency virus/AIDS are limited, particularly in the MENA region. According to the World Health Organization Regional Committee for Africa report, some fundamental key basic knowledge gaps need to be underlined. They include inequalities in oral health, low priority for oral health, lack of adequate funding, inadequate dental student training, obstacles to medical and dental research, and poor databases. There are very few effective public prevention and oral health promotion programs in the AMER. Universal health coverage is not achievable without scientific research on the effectiveness of health promotion interventions.